Animalism new essays on persons, animals, and identity - Blatti, Stephan 1975-; Snowdon, Paul F. (Oxford University Press, 2016)
What are we? What is the nature of the human person? Animalism has a straightforward answer to these long-standing philosophical questions: we are animals. In this publication, fifteen philosophers offer new essays exploring this increasingly popular view, some defending animalism, others criticising it and others exploring its more philosophical implications